Catholic War Discourse in the German “Sonntagsblatt” of the Silesian Diocese Breslau during the First World War of 1914–1918 - Maik Schmerbauch (Wrocławski Przegląd Teologiczny)
The First World War, 1914–1918, demanded that even the Breslau (Polish: Wrocław) Catholic Church give answers to their millions of faithful at home and the soldiers at the front how to value the war in theological and religious terms. “Sonntagsblatt,” the Catholic weekly published during the entire Great War period a large number of articles on this problem. Herewith we attempt to analyse how the Breslau clergy used the “Sonntagsblatt” to give spiritual support.